GENESIS OF THE OFFENCE OF FAMILY VIOLENCE IN THE SERBIAN CRIMINAL LAW - Samardžić, Stefan; Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Serbian criminal law legislature regulating family violence has been riddled with shortfalls and ambiguity from the onset, resulting in major difficulties in its application. Insufficient rumination by lawmakers and absence of wider discussion within professional circles is evident in the criminal law provisions regulating this pathology. An overview of provisions regulating the family law offence in fundamental criminal codes offers somewhat better insight into the difficulties of applying such provisions in practice in addition to offering an explanation on how the public views family violence. Further this overview sheds light on some of the reasons for development of special, and in many ways hybrid, legislature regulating family violence.
Keywords: family violence, criminal law, Serbia.